Medical vocation, beyond the duty of care: a review of literature from ethical and philosophical perspectives: Vocación médica, más allá del deber de cuidar: Revisión de la literatura desde el aspecto ético y filosófico - Ayala Garcia, Ricardo Jonathan (2023)
This review article explores medical vocation as a phenomenon that extends beyond the mere duty of caring for patients, focusing on the significance of ethical commitment, empathy, and resilience in medical practice. The implications for medical training and clinical practice are discussed.